Implementasi Manajemen Produksi Bersih Berbasis Value Engineering Sebagai Upaya Meningkatkan Daya Saing Umkm Kripik Tempe Di Kabupaten Ngawi - Nur Baladina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
Each company has the goal of producing quality products with lower production costs. This activity aims to improve the competitiveness of UMKM Kripik Tempe Ngawi through the implementation of cleaner production management based on value engineering, so that the production efficiency is achieved and the company's competitiveness increases. Value engineering in tempe chips production is done by replacing tempe chopping process which was done manually and rely on labor, to use automatic tempe chopper machine. The results shows that the value engineering through the use of automatic tempe chopper machine can save the production cost of Rp 287,07 for each big tempe chips pack and Rp 75,54 for each small packed tempe chips, or save production cost until Rp 44.434,73 per day. Assuming that the company's revenue is fixed, the implementation of value engineering will have a positive impact to increase of tempe chips manufacturer's profit, so that UMKM partners are advised to apply cleaner production management based on value engineering to achieve expected profit target and to improve business competitiveness.